Integrasi Sistem Pertanian Dan Perikanan (Minapadi) Sebagai Strategi Peningkatan Produktivitas Dan Keberlanjutan Pangan - Zebua, Septerina Putri; Zebua, Dermawan (CV. SINAR HOWUHOWU, 2026)
The agriculture and fisheries sectors are key pillars in supporting national food security, particularly in an agrarian and maritime country like Indonesia. However, both sectors still face various structural challenges, including limited land, environmental degradation, and low production efficiency. One innovative approach being developed to address these issues is the integrated farming and fisheries system, specifically through the minapadi (rice-fish farming) system. This research aims to analyze the contribution of the minapadi system to increased productivity, resource efficiency, and environmental sustainability. The research method used is a qualitative descriptive approach supported by quantitative data obtained through field observations, farmer interviews, and documentation studies.